Head injury evaluation strategy for sepak takraw ball heading: a systematic review - N.M.H.M., Hassan; Nasrul Hadi, Johari; M.N., Omar; M.H.A., Hassan; Z., Ahmad@Manap (IET, 2023)
Since Sepak Takraw was introduced in 1965 in South East Asian Peninsular (SEAP) Games, the players have intensively trained the heading ball as the main movement during the game. The impacts of repetitive Takraw ball heading, however, can lead to brain traumatic injuries such as concussion, internal bleeding and dizziness. This article set out the current trend and research gap on head impact injury during sepak takraw ball heading. Guided review method using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) Statement has identified 26 related studies from Scopus, Web of Science, and PubMed databases. This review from 2014 to 2021 resulted in only one article has been carried out on sepak takraw ball heading head injury and 25 articles on soccer and lacrosse. Six main themes have resulted from further review of the articles in measurement strategy, type of head impact, measurement tool, output data, subject category, and head protector in sepak takraw to study the ball heading head impacts. A total of 26 sub-themes further has been produced by the six themes.Several recommendations are proposed to conduct laboratory experimental studies considering ball-to-head heading only and studying headband for concussion reduction considering both linear and angular kinematics as the head injury predictors.